Emission factor determination and application for materials associated with producing beer - Noel, Quincy, author; Toman, Elizabeth Myers, advisor; Gifford, Lauren, committee member; Dillon, Jasmine, committee member (Colorado State University. Libraries, 2025)
This thesis uses openLCA software with the ecoinvent and Agribalyse databases and the TRACI impact assessment method to determine cradle-to-gate emission factors for key materials and processes in beer production. It focuses on upstream ingredients and energy inputs, excluding brewing operations, packaging, and distribution, to create a modular toolkit (i.e., individual emission factors adaptable to brewery-specific inputs) for breweries in Northern Colorado aiming to reduce environmental impacts. Greenhouse gas emissions and eutrophication are analyzed. While not a full life cycle assessment, this study promotes more equitable access to sustainability metrics and provides a foundation for future carbon footprints, hotspot analyses, and brewery-level emissions inventories.
Keywords: openLCA; TRACI; Agribalyse; ecoinvent; beer; emissions; GWP; eutrophication; upstream; brewery